Negative ion source development for a photoneutralization based neutral beam system for future fusion reactors. (12th December 2016) - Simonin, A; Agnello, R; Bechu, S; Bernard, J M; Blondel, C; Boeuf, J P; Bresteau, D; Cartry, G; Chaibi, W; Drag, C; Duval, B P; de Esch, H P L; et al.
Abstract: In parallel to the developments dedicated to the ITER neutral beam (NB) system, CEA-IRFM with laboratories in France and Switzerland are studying the feasibility of a new generation of NB system able to provide heating and current drive for the future DEMOnstration fusion reactor. For the steady-state scenario, the NB system will have to provide a high NB power level with a high wall-plug efficiency ( η  ∼ 60%). Neutralization of the energetic negative ions by photodetachment (so called photoneutralization), if feasible, appears to be the ideal solution to meet these performances, in the sense that it could offer a high beam neutralization rate (>80%) and a wall-plug efficiency higher than 60%. The main challenge of this new injector concept is the achievement of a very high power photon flux which could be provided by 3 MW Fabry–Perot optical cavities implanted along the 1 MeV D − beam in the neutralizer stage. The beamline topology is tall and narrow to provide laminar ion beam sheets, which will be entirely illuminated by the intra-cavity photon beams propagating along the vertical axis. The paper describes the present R&D (experiments and modelling) addressing the development of a new ion source concept (Cybele source) which is based on a magnetized plasma column. Parametric studies of the source are performed using Langmuir probes in order to characterize and compare the plasma parameters in the source column with different plasma generators, such as filamented cathodes, radio-frequency driver and a helicon antenna specifically developed at SPC-EPFL satisfying the requirements for the Cybele (axial magnetic field of 10 mT, source operating pressure: 0.3 Pa in hydrogen or deuterium). The paper compares the performances of the three plasma generators. It is shown that the helicon plasma generator is a very promising candidate to provide an intense and uniform negative ion beam sheet.